2‐D Analytical solutions for the multisegmented panel subjected to arbitrary boundary condition. Issue 2 (7th November 2022) - Kumar, Viwek; Kumari, Poonam
Abstract: A closed‐form bending solution of the multisegmented panels is presented for different support conditions. The panels can have multiple no. of segments along the x ‐axis with varying material properties. The governing equations are formulated using the extended Kantorovich method (EKM) in the mixed‐form, and a set of ordinary differential equations have been obtained. The continuity of displacement and stresses are satisfied at the interface of each segment. The panels can have simply‐support, clamp, and free types of support conditions. The panel interface at each segment along the x ‐axis is assumed to be perfectly bonded. In this work, the stress and deformation variations for four types of panel configuration have been studied. Two segmented panels having aluminum and Graphite–Epoxy with equal and unequal segments are considered. A four‐segmented Al/SiC panel having gradual material variation is also analyzed. The effect of ply‐angles on the longitudinal variables is also studied for the equal segmented Al/GrEp panel. The deflection and stresses are compared with the finite element solution and found in good agreement with the EKM results. The current development will lead to developing the solution for stepped panels, dissimilar plates, and more complex cases used in aerospace applications. Abstract : A closed‐form bending solution of the multisegmented panels is presented for different support conditions. The panels can have multiple no. of segments along the x ‐axis with varying material properties. The governing equations are formulated using the extended Kantorovich method (EKM) in the mixed‐form, and a set of ordinary differential equations have been obtained. The continuity of displacement and stresses are satisfied at the interface of each segment. The panels can have simply‐support, clamp, and free types of support conditions.…